Open Software for Chemical and Electrochemical Modeling: Opportunities and Challenges. (January 2019) - DeCaluwe, Steven C.
Abstract : Recent advances in open source software capabilities, concurrent with advances in computational chemistry and operando diagnostics, provide new opportunities for modeling complex electrochemical phenomena. These capabilities include (i) new tools for modeling electrochemical processes; (ii) software for efficient and powerful numerical simulation, analysis, and visualization; (iii) and software ecosystem tools to enable efficient management and development of new computational tools. Herein, we highlight some of the open source software tools relevant to electrochemical simulations and demonstrate these capabilities within the context of modeling the growth of the solid electrolyte interphase in lithium ion batteries. Finally, we discuss the future outlook for open source software tools within the context of data science and electrochemistry research.